INTESTINAL MICROBIOTA AS A BIOMARKER OF HEALTH: AGE-SPECIFIC PROFILES AND FUNCTIONAL IMPACTS - Yorkinoy Mirzahamdamovna, Niyazova (PT. Antis International Publisher, 2024)
Objective: The purpose of this research is to investigate the age-specific makeup, functional functions, and impact of the human intestinal microbiota on health outcomes over the life course. Method: Microbiota profiles at various life stages, from infancy to old age, were analyzed in a thorough assessment of recent research, with an emphasis on their effects on immune function, metabolism, and disease susceptibility. Results: The results show that each life stage has unique microbial populations that help control important physiological functions. Age-related changes in immunological responses, metabolic regulation, and heightened vulnerability to chronic illnesses are specifically correlated with changes in microbial composition. Novelty: The diagnostic potential of microbiota profiling is highlighted in this review, which also provides fresh perspectives on individualized healthcare strategies. By improving the management of chronic diseases and encouraging healthier aging, the incorporation of microbiota-based approaches into clinical practice may offer more accurate diagnoses and therapeutic interventions for age-related health concerns.